The language of empire myths and metaphors of popular imperialism, 1880-1918 - MacDonald, Robert H. 1934- (Studies in imperialism, 2017)
During the last thirty years of the nineteenth century the British Empire increased enormously and by 1900 the Empire covered a fifth of the world's land surface. In Britain itself, the growth of Empire came to the centre of the political debate and was applauded by a largely sympathetic press. Two sides of imperialism had emerged - the acquisition of territory and a campaign of propaganda to make imperialism 'popular'. Both are the subject of this book. 'The Language of Empire' describes how the Empire was constructed and given shape and meaning for its contemporaries. The author explores how the imperial 'story' was imagined and how the day-to-day activities of its participants were understood. He focuses on both the face of Empire as it was presented to the public, and at the lives of individual imperial soldiers or adventurers, exploring how the idea of Empire gave meaning to the actions of its participants. The author defines the role of discourse in determining this perception of reality - looking at the construction of Empire though the huge body of popular texts ranging from fiction, poetry and children's stories to history and biography. This study will appeal to readers interested in British imperialism, those engaging in literature and cultural studies as well as to specialists in colonial history